Benefits of the Global Integration Method (Método de Integração Global - MIG) in functional priorities of parents of Brazilian children and adolescents with autism spectrum disorder - Amanda Aparecida Alves Cunha Nascimento; Deisiane Oliveira Souto; Thalita Karla Flores Cruz; Arthur Felipe Barroso de Lima; Gabriela Silva Oliveira; Vitor Geraldi Haase (BMC Pediatrics)
Abstract Background Understanding the priorities of parents of children and adolescents with autism spectrum disorder (ASD) is crucial for implementing evidence-based programs. This study aims to identify the functional priorities of parents of Brazilian children and adolescents with ASD, analyze variations in priorities according to the levels of support and age groups of the participants, and categorize the goals according to the categories of the International Classification of Functioning, Disability, and Health (ICF). Additionally, this study aimed to evaluate changes in parents’ performance and satisfaction with functional priorities after intervention with the Global Integration Method (Métodode Integração Global - MIG). Methods A total of 241 children/adolescents with ASD (mean age, 6.92 ± 3.61 years) were recruited from different regions of Brazil. 76% (76%) were male, and 40.7% were classified as having support level 2. The Canadian Occupational Performance Measure was administered to parents/caregivers to identify their priorities for their children and to assess changes in performance and satisfaction with priorities after intervention with MIG. The MIG protocol consisted of functional task training in a naturalistic environment (City of Tomorrow) combined with the use of a flexible therapeutic suit (MIG Flex) and was conducted for 3 months, five times a week, for 3–4 h per day. Descriptive statistics were used to provide the priority profile. Pre- and post-intervention data were analyzed using paired t-test. Results Parents established 1,203 functional priorities. Activities of daily living, behavioral difficulties, communication, play, and social interactions were the main functional priorities in the perception of parents/caregivers. The profiles of functional priorities were similar between the different levels of support and age groups. Approximately 64% of the priorities were classified in the activity domain of the ICF. In general, the MIG program resulted in significant improvements in performance and satisfaction for the majority of functional priorities (p < 0.05). Conclusion Activities of daily living appear to be the main priority of parents of children and adolescents with ASD, regardless of the level of support or age group. The MIG program has been associated with improvements in performance and satisfaction across several of the functional priorities identified by parents.